Household wealth distribution in Italy in the 1990s - Andrea Brandolini; Luigi Cannari; Giovanni d'Alessio; Ivan Faiella (Levy Economics Institute of Bard College, 2004)
This paper describes the composition and distribution of household wealth in Italy. First, the evolution of household portfolios over the last 40 years is described on the basis of newly reconstructed aggregate balance sheets. Second, the characteristics and quality of the main statistical source on wealth distribution, the Bank of Italy's Survey of Household Income and Wealth, are examined together with the statistical procedures used to adjust for nonresponse, nonreporting and underreporting. The distribution of household net worth is then studied using both adjusted and unadjusted data. Wealth inequality is found to have risen steadily during the 1990s. The increased concentration of financial wealth was an important factor in determining this path.
Keywords: D31; 330; household wealth; wealth inequality; Italy